How green bond issuance affects China's transportation industry - an empirical study based on China's transportation industry from 2017 to 2021 - Niu, Shusen (2023)
Starting in 2016, China began to introduce a series of policies regarding the green development transition and set a 2030 target to achieve peak carbon target by 2030 and a carbon neutral target by 2060. This has also released a strong signal for a number of companies to transform. As a result, many companies have to seize the train of the times and have embarked on a transformation path. During the transition period, enterprises need a lot of financial support, and many enterprises and banks have started to explore innovative green financial products to obtain sources of funding to achieve the transition. This paper focuses on examining the impact of green bonds on China's transportation industry between 2017 and 2021 by using a multipoint difference approach and a conditional value-at-risk model. Our preliminary analysis and empirical evidence on the impact of green bond issuance on the Chinese transportation industry between 2017 and 2021 reveals that: (1) the financing method of green bond issuance can reduce the financing cost of Chinese transportation enterprises; (2) green bond issuance does not have a significant impact on the performance of Chinese transportation enterprises; (3) the Chinese transportation stock market is the Granger cause of the green bond issuance market, and its risk spillover fluctuations will have a positive impact on the green bond market, while the green bond issuance market does not bring volatility to the Chinese transportation stock market. Finally, based on the analysis of the above findings, we put forward relevant recommendations for green bond issuance from the perspectives of enterprises, government and investors.